Viral hepatitis C pandemic: Challenges and threats to its elimination - Krekulova, Laura; Honzák, Radkin; Riley, Lee W (Journal of viral hepatitis, 2021)
Under the WHO plan, the global elimination of the HCV pandemic is scheduled for 2030. The burden of HCV infection in developed countries is largely borne by people who inject drugs (PWID): new infections and reinfections are related to their risky behaviour. Although safe and sensitive hepatitis C diagnostic tools and directly acting antiviral medication are widely used, major challenges to disease elimination still remain in developed countries, where the WHO plan is in progress. The challenge is in the involvement and engagement of infected PWID. There is a strong need to change our uptake and treatment strategies to address all patients from the risk groups, connect them with the healthcare system and cure them with the vision to eliminate this HCV pandemic.
Keywords: intravenózní abúzus drog; pandemie; Antiviral Agents; Substance Abuse, Intravenous; lidé; Hepacivirus; hepatitida C; HCV pandemic; Hepatitis C; WHO HCV elimination plan; Pandemics; HCV elimination; antivirové látky; Hepatitis C virus; Humans